Mapping the Past: Eduard Paulus the Elder (1803–1878) and the Archaeological Survey of Württemberg - Frauke Kreienbrink (Bulletin of the History of Archaeology, 2007)
In 1858 Karl Eduard Paulus caused a minor sensation at the annual meeting of the General Association of German Antiquarian Societies (Gesamtverein deutscher Geschichts- und Alterthumsvereine, from now on referred to simply as the General Association) by presenting his archaeological map of the Kingdom of Württemberg, in south-western Germany. It was the first detailed map of an entire German state to record archaeological monuments. Systematic archaeological surveys and mapping of monuments and finds had occasionally been produced by scholars from the early nineteenth century, and some archaeological maps already existed for some regions; but Paulus’ map, published in 1859, was exceptional. In this paper I will point out what was so new about this map. Moreover I will examine how the antiquarian research of Paulus in general, and his archaeological map in particular, were integrated into his extensive concept of the natural and cultural landscape. And I will discuss whether there were special conditions in Württemberg that promoted such enterprises – or whether this enterprise was the consequence of the private initiative of an individual.